2022
DOI: 10.1039/d2ta06038h
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the structural evolution mechanism and potassium storage performance of expanded graphitic onion-like carbon

Abstract: Although expanded graphite prepared from flake graphite has been well developed, the expanded mechanism of graphite with confined structure has not been well researched. Herein, we systematically reveal how the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Graphitic onion-like carbon (GOC) was prepared from pyridine by one-step injection pyrolysis and subsequent graphitization. , The oxidized graphitic onion-like carbon (O-GOC) was prepared by the modified Hummer’s method from GOC . Then, the O-GOC sample was carbonized at 300, 500, and 700 °C kept for 1 h with a heating rate of 2 °C min –1 in a N 2 atmosphere to obtain a series of mild-expanded graphitic onion-like carbon (MEGOC) samples, which are denoted as MEGOC300, MEGOC500, and MEGOC700, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Graphitic onion-like carbon (GOC) was prepared from pyridine by one-step injection pyrolysis and subsequent graphitization. , The oxidized graphitic onion-like carbon (O-GOC) was prepared by the modified Hummer’s method from GOC . Then, the O-GOC sample was carbonized at 300, 500, and 700 °C kept for 1 h with a heating rate of 2 °C min –1 in a N 2 atmosphere to obtain a series of mild-expanded graphitic onion-like carbon (MEGOC) samples, which are denoted as MEGOC300, MEGOC500, and MEGOC700, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously prepared expanded graphitic onion-like carbon with superior electrochemical properties by rapid thermal reduction. However, the large specific surface area of expanded graphitic onion-like carbon makes its initial Coulombic efficiency low (∼18%) . Further structural optimization is required to improve the electrochemical properties of GOC by increasing the initial Coulombic efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright © 2015, American Chemical Society; b) Structural transition from GOC to EGOC. [32] Reprinted from Meng et al, with permission. Copyright © 2022, Royal Society of Chemistry; c) Schematic illustration of the evolution of the surface on the graphite.…”
Section: Graphitic Carbon Materialsmentioning
confidence: 99%
“…Besides, Meng et al demonstrated the transformation of confined graphite into a bamboo shoot-like structure using Hummers oxidation and rapid thermal expansion with graphitic onion-like carbon (GOC). [33] The polyhedral structure and interlaced graphitic layers of GOC restrict the escape of gas, forming expanded graphitic onion-like carbon (EGOC) with a helical structure and numerous wavy wrinkles (Figure 3a). The work provides a highperformance expanded graphite electrode for developing and applying potassium-ion energy storage systems.…”
Section: Graphitementioning
confidence: 99%